Struktur Sastra Lisan Tembang Naseb Anak Mude dan Tige Serangkai di Desa Ujan Mas Kabupaten Muara Enim - Dessy Wardiah; Hetilaniar Hetilaniar (LP4MK STKIP PGRI Lubuklinggau, 2021)
Rambang is a part of the province of South Sumatra. Rambang has a wealth of diverse literature and culture, one of which is the songs Naseb Anak Mude and Tige Serangkai in Ujan Mas Village, Muara Enim Regency. Therefore, the purpose of this study was to describe the structure of the oral literature of the songs Naseb Anak Mude and Tige Serangkai. The research method uses qualitative content analysis methods. The research data collection technique used documentation techniques obtained by recording oral literature of the Naseb Anak Mude and Tige Serangkai songs in Ujan Mas Village, Muara Enim Regency. Based on the results of the study, it shows that the Naseb Anak Mude and Tige Serangkai songs in Ujan Mas Village, Muara Enim Regency have a unique structure, especially the physical structure which has a meter shape, meaning that the form of the song does not change, both from the type of rhyme ab, ab and in terms of rows only consists of four lines.